Post-Keynesian economics : new foundations - Lavoie, Marc (Cheltenham Edward Elgar Publishing Ltd., 2014)
The book is a considerably extended and fully revamped edition of the highly successful and frequently cited Foundations of Post-Keynesian Economic Analysis, published in 1992. It provides an exhaustive account of post-Keynesian economics and of the developments that have occurred in post-Keynesian theory and in the world economy over the last twenty years. Topics covered include open-economy issues, the methodological foundations of heterodox economics, consumer theory, firms and pricing, money and credit, effective demand and employment, inflation theory, and growth theories
Preface 1. Essentials of Heterodox and Post-Keynesian Economics-- 2. Theory of Choice -- 3. Theory of the Firm -- 4. Credit, Money and Central Banks -- 5. Effective Demand and Employment -- 6. Accumulation and Capacity -- 7. Open-Economy Macroeconomics -- 8. Inflation Theory -- 9. Concluding Remarks -- Index
Revision of the author's Foundations of post-Keynesian economic analysis
Includes bibliographical references (P. 585-646) and indexes
Keywords: Economics; KEYNESIAN ECONOMICS